Optimization of Material Recovery Strategies in the Demolition Phase of Buildings – A Case Study - Rajan D; Dr. M. Kranti Kumar; Dr. S. Ramesh (International Journal of Engineering and Management Research, 2021)
Globally, the construction industry is one of the most environmentally catastrophic industries, with a significant effect on the raw materials usage, their commitment of use throughout their whole life cycle, and the atmosphere in which they work. Between 1950 and 2010, global average material consumption rose from 5.0 t to 10.3 ton per capita per year, owing to population growth, industrialization, and increased socio-economic strength. Moreover, this industry uses 35% of produced energy and releases 40% of carbon dioxide into the Earth's atmosphere. One hundred fifty million tons of CDW is made in India according to the BMPTC, and less than 1% is reutilized properly added to that the 55% of total solid waste in India are from the construction industry. The waste produced during the demolition can be well utilized if managed and appropriately recovered, which directly reduces the virgin raw material usage in the new construction, decreasing the amount ending in the landfill. This study aims to understand the strategies and technology for material recovery after the building's life. The literature review will be taken up to list the different strategy in practice for material recovery. The techniques for material recovery are discussed to understand more in detail. This research helps find the other methods for material recovery and equipment and technology during the demolition and reconstruction of the RCC framed structure. The bottlenecks in the adoption of the various strategy are studied in this research.